Tinjauan Yuridis Terhadap Perjanjian Jual Beli Online Dengan Jasa M- Bangking - Nafturahma , Nadya AL; Safitri , Latipah Nurma; Parolita, Inka; Dania , Rahma; Sari , Yetri Oktiva (Universitas Dehasen Bengkulu, 2024)
This study aims to find out what the legal standing is for online buying and selling agreements through M-banking and to find out what the legal consequences are for online buying and selling fraud. The research method used in this research is normative research with descriptive research type. The approach used is a statutory approach (statue approach) and a doctrinal/conceptual approach. The type of data used is secondary data which consists of primary legal materials, secondary legal materials, and tertiary legal materials. Data collection was carried out by means of a literature study. Then the collected data were analyzed systematically. According to the results of this study, it shows that: First, online buying and selling agreements in buying and selling forums through M-banking services fulfill the legal requirements of an agreement in accordance with the provisions of Article 1320 of the Criminal Code, which states that part of one of the legal requirements of an agreement is that there is an